Herquline A, produced by Penicillium herquei FKI-7215, exhibits anti-influenza virus properties. Issue 1 (2nd January 2017) - Chiba, Takuya; Asami, Yukihiro; Suga, Takuya; Watanabe, Yoshihiro; Nagai, Takayuki; Momose, Fumitaka; Nonaka, Kenichi; Iwatsuki, Masato; Yamada, Haruki; Ōmura, Satoshi; Shiomi, Kazuro
Abstract: In the course of screening for new anti-influenza virus antibiotics, we isolated herquline A from a culture broth of the fungus, Penicillium herquei FKI-7215. Herquline A inhibited replication of influenza virus A/PR/8/34 strain in a dose-dependent manner without exhibiting cytotoxicity against several human cell lines. It did not inhibit the viral neuraminidase.